Pengembangan Media Pembelajaran Tajwid dengan Aplikasi TikTok Menggunakan Model ADDIE - Adi Irwandi; Muhammad Yusuf Yunus (Universitas Al Asyariah Mandar, 2025)
This research explores the use of the TikTok application to develop tajwid learning media, especially on lam ta'rif material, in class VII of SMP Negeri 7 Polewali. The resulting learning media aims to support the teaching and learning process, making it easier for teachers to convey material in an interesting way. The research process follows the stages of the ADDIE development model, which consists of: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of the research show that tajwid learning media about lam ta'rif has been successfully developed. The feasibility assessment by media expert validators achieved a score of 68 out of 80 (85% feasible), while the assessment by material expert validators obtained a score of 65 out of 80 (81.2% feasible). At the implementation stage, the average assessment based on student responses in the trial was 19.06 with a percentage of 95.3% (very feasible).